Desempenho do setor industrial exportador brasileiro pela ótica de hysteresis: (1999-2007) - Jubert, Roberto Wagner (2009)
This thesis had as main objective to identify the existence of hysteresis in exports of the Brazilian industrial sector. Therefore, we performed a descriptive analysis of exports (free on board), the quantities exported ( quantum ) and price indices, as well as the estimation of parameters of fractional differentiation to measure hysteresis. Of descriptive analysis is demonstrated evidence of hysteresis after the year 1999 in industrial exports, moreover, is not apparent persistence of medium-sized companies in periods of unfavorable exchange rate and persistence of large companies. The results of estimations corroborate the descriptive analysis identify hysteresis with partial effects for the period 1999-2002 and hysteresis for the period 2003-2007. Of the industries studied, two groups were prominent exporters of industrial products, with group 1 for sectors that have characterized the transition from partial to hysteresis with hysteresis effects.